Simulation of single phase AC induction motor (capacitor start) by using MATLAB Simulink: article / Amir Hanifa Hussin - Hussin, Amir Hanifa (Universiti Teknologi MARA (UiTM), 2010)
This technical report will discuss the basic operation of an AC single phase induction motor and the capacitor start single phase AC induction motor. Besides that, this report also will discuss about the characteristic of single phase induction motor for the capacitor start type including the torque, speed and current. For this project, Matlab Simulink will be used as a simulator